Management strategies to curb rhino poaching: Alternative options using a cost–benefit approach - Ferreira, Sam M.; Pfab, Michèle; Knight, Mike (South African Journal of Science, 2014)
The combination of increasing demand and high black market prices for rhino horn in Asian markets has fueled an escalation in rhino poaching since 2007, particularly in South Africa. This situation has in turn resulted in greatly increased rhino protection costs, loss in confidence by the private sector in rhinos, loss of revenue to conservation authorities and reduced rhino population growth rates. Within current CITES processes, management responses to threats posed by poaching to rhino persistence fall within a mixture of reactive responses of increased protection and law enforcement and some pro-active responses such as demand reduction tactics, along with a parallel call for opening a legal trade in horn. These rhino management strategies carry different risks and benefits in meeting several conservation objectives. An expert-based risk–benefit analysis of five different rhino management strategies was undertaken to assess their potential for delivering upon agreed rhino conservation objectives. The outcomes indicated that benefits may exceed risks for those strategies that in some or other format legally provided horn for meeting demand. Expert risk–benefit approaches are suggested to offer a rational, inclusive and consensus generating means of addressing complex issues such as rhino poaching and augmenting the information used within the CITES decision-making processes.